Pengaruh Konsentrasi Ekstrak Daun Kelor (Moringa oleifera) Terhadap Karakteristik Bolu Kukus Labu Kuning (Cucurbita moschata) - Baharudin, Rehal B; Ega, La; Tuhumury, Helen C D (Universitas Pattimura, 2023)
Steamed sponge cake is one of the foods made from wheat flour, which until now has been imported. The use of wheatflour in steamed sponge cakes can be reduced by using local foods such as pumpkin and moringa leaves, which also add nutrition al value to steamed sponge cakes. The purpose of this study was to determine the concentration of Moringa leaf extract that is right for producing pumpkin steamed sponge cake with the best characteristics. This study used CRD, which consisted of one factor, namely the concentration of Moringa leaf extract, with 5 levels of treatment as follows: K0 = 0%, K1 = 25%, K2 = 50%, K3 = 75%, and K4 = 100%. The results showed that K2 treatment (50% moringa leaf extract) can produce the best pumpkin steamed sponge cake. Based on its physicochemical characteristics, the addition of 50% moringa leaf extract resulted in a steamed sponge cake with a moisture content of 43.76%, an ash content of 0.30%, a protein content of 7.42%, a fat content of 2.70%, a carbohydrate content of 45.80%, and a specific volume of 2.31 mL/g. Based on its sensory characteristics, steamed pumpkin sponge cake with 50% moringa leaf extract was liked (3.6) forits slight green color (3.1), liked (3.8) forits slight moringa taste (3.2), liked (4.0) forits soft texture (3.9), liked (3.5) forits slight moringa aroma (2.9), and liked (3.7) on its overall characteristics.